Trends in use and outcome of postoperative radiotherapy following mastectomy: A population-based study. Issue 1 (January 2017) - Corradini, Stefanie; Bauerfeind, Ingo; Belka, Claus; Braun, Michael; Combs, Stephanie E.; Eckel, Renate; Harbeck, Nadia; Hölzel, Dieter; Kiechle, Marion; Niyazi, Maximilian; Engel, Jutta
Abstract: Purpose: The objective of the present population-based study was to evaluate the role and effectiveness of postmastectomy radiation therapy (PMRT) in clinical practice. Methods: The study included 16, 675 patients diagnosed with invasive breast cancer from 1988 to 2012 and resident within the catchment area of the Munich Cancer Registry. Use of PMRT, local recurrence-free survival (LRFS), cumulative incidence of time to local recurrence, relative survival and conditional overall survival (cOS), were analysed for different time periods (1988–1997 and 1998–2012). Results: Variables favouring the use of PMRT on multivariate logistic regression analysis included young age, large tumour size, positive resection margin and positive nodal status. Over time, a significant increase of PMRT was registered for patients with ⩾4 positive lymph nodes. Moreover, the present findings track a less frequent use of PMRT in elderly patients. After adjusting for age, tumour characteristics and therapies, the Cox regression analysis for LRFS identified PMRT as an independent predictor for improved local control (HR: 2.145; 95% CI: 1.787–2.574, p < 0.0001). Patients with 1–3 involved lymph nodes had a 10-year cumulative incidence of local recurrence of 13.7% following mastectomy, compared to 6.5% following PMRT ( p = 0.0001). Comparable findings were obtained for patients presenting with ⩾4 positive lymph nodes. All effects were smaller or extinct in elderly patients aged ⩾70 years. On multivariate analysis for cOS, no significant advantage for PMRT could be detected (HR: 1.084; 95% CI: 0.986–1.191, p = 0.095). Conclusion: The present study was useful in providing an overview on trends in the adoption of PMRT over a 25-year period. An increase in the use of PMRT from 1988 to 2012 was observed, especially in high-risk patients with ⩾4 positive lymph nodes. Patients selected for PMRT had an improved local control and an equivalent relative survival compared to patients who had no indication for PMRT.